Longitudinal Outcomes of Gender Identity in Children (LOGIC): study protocol for a retrospective analysis of the characteristics and outcomes of children referred to specialist gender services in the UK and the Netherlands - Victoria Vickerstaff; Michael King; Bridget Young; Rachael Hunter; Gary Butler; Polly Carmichael; Rumana Omar; Veronica Ranieri; Eilis Kennedy; Nastasja De Graaf; Simon Baron-Cohen; Lauren Spinner; et al. (BMJ Open)
Introduction Specialist gender services for children and young people (CYP) worldwide have experienced a significant increase in referrals in recent years. As rates of referrals increase, it is important to understand the characteristics and profile of CYP attending these services in order to inform treatment pathways and to ensure optimal outcomes.Methods and analysis A retrospective observational study of clinical health records from specialist gender services for CYP in the UK and the Netherlands. The retrospective analysis will examine routinely collected clinical and outcome measures data including demographic, clinical, gender identity-related and healthcare resource use information. Data will be reported for each service and also compared between services. This study forms part of a wider programme of research investigating outcomes of gender identity in children (the Longitudinal Outcomes of Gender Identity in Children study).Ethics and dissemination The proposed study has been approved by the Health Research Authority and London—Hampstead Research Ethics Committee as application 19/LO/0181. The study findings will be published in peer-reviewed journals and presented at both conferences and stakeholder events.